Synthesis of a New Schiff Base‐like Trinucleating Ligand and its Copper, Vanadyl, and Iron Complexes – Influence of the Bridging Ligand on the Magnetic Properties. Issue 21 (16th October 2017) - Weber, Birgit; Kaps, Eike; Dankhoff, Katja
Abstract : A trinucleating Schiff base‐like ligand and its copper(II), vanadyl(IV), iron(II), and μ‐oxido iron(III) complexes were synthesized and characterized in detail. In the case of the hexanuclear iron(III) complex single crystals suitable for X‐ray structure analysis were obtained. For the trinuclear complexes, the m ‐phenlylene linkage of the phloroglucinol unit determines the magnetic exchange interactions. For the copper complex weak antiferromagnetic interactions are observed, whereas the corresponding trinuclear vanadyl complex shows weak ferromagnetic exchange interactions. A competition between superexchange interactions and spin‐polarization due to differences in the symmetry of the magnetic orbitals is made responsible for this observation. In the case of the hexanuclear iron(III) complex the exchange interactions via the μ‐oxido bridge dominate leading to strong antiferromagnetic interactions. The corresponding iron(II) complex is a pure high‐spin complex. Abstract :